The effects of aging population on the sustainability of fiscal policy - Mikko Puhakka (Bank of Finland, 2005)
We study the effects of aging population on the sustainability of fiscal policy in overlapping generations models with government debt and a pay-as-you-go pension system.The smaller the population growth rate, the lower the maximum sustainable level of deficits. When the utility function is of a specific form, an increase in the payroll tax rate and the replacement rate decreases the level of maximum sustainable deficits; except in the case when pension depends on the wage level prevailing during the working period.The ratio of the deficits in two economies with different population growth rates is characterized with numerical examples.
URN:NBN:fi:bof-20140807247
Keywords: E21; E32; 330; aging; pensions; overlapping generations; fiscal policy